Qualitative Test of Identification of Borax in Wet Noodles at Traditional Markets in Palembang City - Rosita, Yanti; indriyani, Indriyani; Saleh, Farobby Yusuf (ANATOMICA MEDICAL JOURNAL | AMJ, 2023)
Food is a basic need of human life. Cases of food poisoning and infectious diseases caused by food continue to increase. Borax is a derivative of the heavy metal boron (B) and is generally used as a preservative and bactericidal. One of the tests that can be done to identify foods that contain borax is a test with curcumin paper and a borax test kit. Aim: This research is to identify the presence of borax in wet noodles with a qualitative test in a traditional market in the city of Palembang. Method: The type of research used in this research is descriptive qualitative. Is a type of research that provides an overview or description of the identification of borax in wet noodles. Sampling in this study used primary data by taking samples directly from food vendors who have wet noodles in the 16 Ilir market, Palembang. Sampling used a total sampling technique that met the inclusion criteria. Result: The physical test results showed 16 samples of noodles with a chewy texture, for the color parameter, 13 samples with yellow color were obtained, for the durability parameter, 12 samples lasted 24 hours, and for the olfactory parameter, 16 samples does not have a pungent odor, for the curcumin paper test, 16 samples were yellow and for the borax kit test, 16 samples were orange. Conclusion: The physical test and qualitative test with curcumin paper and the borax kit test showed that there were no wet noodle samples containing borax in 16 ilir market Palembang.Keywords: Borax, Food, Wet noodles